Improving color quality and luminous flux of white LED utilizing triple-layer remote phosphor structure - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
In this manuscript, we presented a research that enhance the performance of WLED using the multi-phosphor configuration. The phosphor layers in the research are separated from each other to achieved better luminous efficiency, however, it makes controlling color light quality more complex. Another issue is finding out the whether two layers of phosphor or three layers of phosphor is better in improving color quality. The research addressed this issue by analyzing the optical aspects of the respective WLEDs that employ these structure. The studied aspects are quality indicators such as luminous efficacy (LE), and color uniformity, color rendering index (CRI), color quality scale (CQS). The results of the experiments in this research, which come from the employment of WLEDs with 2 color temperatures 5600 K and 8500, suggest that WLED with three phosphor layers is better in CRI, CQS, LE. This type of phosphor structure also limits the color deviation significantly, thus, improves the color uniformity. This results is verifies with Mie theory, therefore, can be applied as reference or guideline for production of better WLEDs